Determinação e verificação de ângulos de céu decorrentes dos padrões de ocupação do solo nos bairros de Cabo Branco e Tambaú - João Pessoa-PB - Santos, Janine Holmes dos (2007)
The present research determines and verifies the efficiency of obstructed sky angles due to occupation of the actual area and those related to three other settlements suggested by Peregrino (2005) to a segment of the districts of Cabo Branco and Tambaú on João Pessoa PB. We used the methodology developed by Pereira (1994), based in the scheduled balanced radiation of Aroztegui (1980) and softwares to calculate direct and diffuse radiations together with masks of solar blockage. The research concluded that the law used to conduct the settlement of urban areas of the city of João Pessoa is totally mistaken in relation to the obstructed sky angles because they not only compromise the intra-urban ventilation but significantly rise the local temperature due to prolonged exposition of vertical and horizontal surfaces located in the urban area.